2019
DOI: 10.1155/2019/7651383
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Induces Postoperative Depression and Inhibits Microglial Function in Mice

Abstract: Many patients experience excellent physical recoveries after surgery; however, there are some of them who from suffer mood fluctuation, even depression. Postoperative depression may be resulted from cognitive dysfunction, pain, and a compromised immune system during the surgery. But there is a higher possibility that general anaesthesia may be responsible for the development of depression. Here, we employed one of the most used anaesthetics, propofol, in a mouse model to investigate whether this intravenous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…In contrast, Wu et al 11 found potentially beneficial effects of propofol in reducing microglial inflammation through NMDA receptor inhibition. Nevertheless, taken together, the study by Feng et al 38 and ours are consistent with the notion that a single dose of propofol in C57BL/6 mice does not have enduring antidepressant-like effects.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast, Wu et al 11 found potentially beneficial effects of propofol in reducing microglial inflammation through NMDA receptor inhibition. Nevertheless, taken together, the study by Feng et al 38 and ours are consistent with the notion that a single dose of propofol in C57BL/6 mice does not have enduring antidepressant-like effects.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, our mice and Feng's mice were not subjected to stress or depressive model preconditioning. 38 This may have been a factor in the lack of a salutary effect of propofol on immobility time in our study as well as the study by Feng et al 38 …”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…But propofol, a widely used intravenous anesthetic, has no effects on neuroinflammation and cognition in the Alzheimer’s transgenic model (Mardini et al, 2017 ). Another study showed that propofol-induced postoperative depressive-like behaviors, which is attributed to the inhibition of microglial activation (Song et al, 2019 ). in vitro studies show propofol has neuroprotective effects by attenuating inflammatory response in microglia (Gui et al, 2012 ; Peng et al, 2014 ).…”
Section: How the Microglia Are Activatedmentioning
confidence: 99%